Achieving Financial Wellness through Financial Literacy among University Students in Cape Town - Ian Lyndon Johnson; Chux Gervase Iwu (Economics and Entrepreneurship: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
This study investigated the role of financial literacy in achieving financial wellness among university students in Cape Town, South Africa. Using a post-positivist approach, data was collected through an online survey with 163 respondents. The study examined key components of financial literacy, which included financial knowledge, attitudes, behaviours, and self-efficacy to assess their influence on students’ financial wellness. Findings indicate that while students have a foundational understanding of financial concepts, gaps remain in areas such as debt management, budgeting, and differentiating between needs and wants. These deficiencies contribute to financial stress and may hinder students’ financial well-being. Despite challenges, students remain optimistic about repaying debt after graduation. The study recommends targeted financial literacy interventions, including debt management education, to improve students’ financial outcomes. Additionally, it calls for the integration of financial literacy into university curricula to support long-term financial wellness.